Which Psychological Characteristics Make a Good Geography Teacher in High School? - Jovanović, Tamara; Otašević, Katarina; Ivanović Bibić, Ljubica; Milanković Jovanov, Jelena; Ivkov-Džigurski, Anđelija; Dragin, Aleksandra; Đukičin Vučković, Smiljana; Stajić, Stefan; Lukić, Aco; Kotorčević, Lazar (Geographica Pannonica, 2024)
This study seeks to examine what traits, “myths” and skills pupils will attribute to good geography teachers, and whether their assessments are influenced by gender, age, grade and satisfaction with a teacher. The sample consists of 150 high school pupils in Serbia. The survey consisted of four parts: socio-demographic characteristics, Big Five Inventory, good teacher myths, and good geography teacher skills. The results showed that pupils believe that good geography teachers have to be impartial, friendly and conscientious in the first place. Also, 13 high school teachers were also interviewed. The data are somewhat in line with previous research, but also indicate pupils’ specific expectations of their geography teachers and teachers’ awareness that they are not just ordinary teachers.